Insights into the Properties of Type Ibn/Icn Supernovae and Their Progenitor Channels through X-Ray Emission - Yusuke Inoue; Keiichi Maeda (The Astrophysical Journal)
Type Ibn/Icn supernovae (SNe Ibn/Icn), which are characterized by narrow helium or carbon lines that originated in hydrogen-poor dense circumstellar medium (CSM), provide new insights into the final evolution of massive stars. While SNe Ibn/Icn are expected to emit strong X-rays through the strong supernova (SN)-CSM interaction, the X-ray emission modeling effort has been limited so far. In the present study, we provide broad-band X-ray light curve (LC) predictions for SNe Ibn/Icn. We find that the soft X-ray LC provides information about the CSM compositions, while the hard X-ray LC is a robust measure of the CSM density, the explosion energy, and the ejecta mass. In addition, considering the evolution of the ionization state in the unshocked CSM, a bright soft X-ray is expected in the first few days since the explosion, which encourages rapid X-ray follow-up observations as a tool to study the nature of SNe Ibn/Icn. Applying our model to the soft X-ray LCs of SNe Ibn 2006jc and 2022ablq, we derive that the CSM potentially contains a larger fraction of carbon and oxygen for SN 2006jc than 2022ablq, highlighting the power of the soft X-ray modeling to address the nature of the CSM. We also discuss detectability and observational strategy, with which the currently operating telescopes such as NuSTAR and Swift can offer an irreplaceable opportunity to explore the nature of these enigmatic rapid transients and their still-unclarified progenitor channel(s).